Whole genome sequence analysis reveals high genomic diversity and potential host-driven adaptations among multidrug-resistant Escherichia coli from pre-weaned dairy calves - Lee, Katie Y.; Schlesener, Cory L.; Aly, Sharif S.; Huang, Bihua C.; Li, Xunde; Atwill, Edward R.; Weimer, Bart C. (Frontiers in Microbiology, 2024)
Food-producing animals such as dairy cattle are potential reservoirs of antimicrobial resistance (AMR), with multidrug-resistant (MDR) organisms such as Escherichia coli observed in higher frequency in young calves compared to older cattle. In this study, we characterized the genomes of enteric MDR E. coli from pre-weaned dairy calves with and without diarrhea and evaluated the influence of host-level factors on genomic composition. Whole genome sequence comparative analysis of E. coli (n=43) revealed substantial genomic diversity that primarily clustered by sequence type and was minimally driven by calf diarrheal disease status (healthy, diarrheic, or recovered), antimicrobial exposure, and dietary zinc supplementation. Diverse AMR genes (ARGs)including extended-spectrum beta-lactamase genes and quinolone resistance determinantswere identified (n=40), with unique sets of ARGs co-occurring in gene clusters with large AMR plasmids IncA/C2 and IncFIB(AP001918). Zinc supplementation was not significantly associated with the selection of individual ARGs in E. coli, however analysis of ARG and metal resistance gene pairs identified positive associations between certain aminoglycoside, beta-lactam, sulfonamide, and trimethoprim ARGs with acid, tellurium and mercury resistance genes. Although E. coli in this study lacked the typical virulence factors of diarrheagenic strains, virulence genes overlapping with those in major pathotypes were identified. Among the 103 virulence genes detected, the highest abundance and diversity of genes corresponded to iron acquisition (siderophores and heme uptake). Our findings indicate that the host-level factors evaluated in this study were not key drivers of genomic variability, but that certain accessory genes in enteric MDR E. coli may be enriched. Collectively, this work provides insight into the genomic diversity and host-microbe interface of MDR E. coli from preweaned dairy calves.